Penerapan Budaya Piket Simpatik Sebagai Pembentukan Karakter Disiplin Siswa - Awallul Mar'atus Sholekah; Nikmah, Khoirun (Al Mabhats : Jurnal Penelitian Sosial Agama, 2023)
Abstract: The purpose of this study is to look at how the Sympathetic Picket Culture is being implemented as a discipline and character-building technique for class X students at SMA Muhammadiyah 1 Ponorogo. The Sympathetic Picket Culture is developed with the objective of providing an unpretentious, humanist learning environment that promotes the development of students' disciplinary character. The research approach used involves studies gathered from various journals as well as the findings of internship interviews linked to the topic of discussion, which are then finished. The findings demonstrate that implementing the Sympathetic Picket Culture has a variety of effects on the development of the disciplinary character of class X students. The sympathetic picket culture, as a cultural practice, aims to improve communication among all members of the school community. This approach is also supposed to improve discipline, resulting in a more pleasant educational environment. The study's findings suggest that tweaks and enhancements to the implementation of the Sympathetic Picket Culture are required to increase its effectiveness in forming the disciplinary character of class X students. As a result, the findings of this study can provide useful guidance for the future development of the character-building program at SMA Muhammadiyah 1 Ponorogo. Abstrak: Penelitian ini bertujuan untuk meneliti penerapan Budaya Piket Simpatik sebagai strategi pembentukan karakter disiplin pada siswa kelas X di SMA Muhammadiyah 1 Ponorogo. Budaya Piket Simpatik diimplementasikan dengan harapan menciptakan lingkungan belajar yang bersahaja, humanis, dan mendukung perkembangan karakter disiplin siswa. Metode penelitian yang digunakan mencakup kajian yang diperoleh dari beberapa jurnal dan hasil wawancara magang 1 yang berkaitan dengan topik pembahasan. Hasil penelitian menunjukkan bahwa penerapan Budaya Piket Simpatik memberikan dampak yang bervariasi pada pembentukan karakter disiplin siswa kelas X. Budaya piket simpatik, sebagai sebuah praktik budaya di SMA Muhammadiyah 1 Ponorogo, diimplementasikan dengan tujuan memperkuat komunikasi di antara seluruh anggota komunitas sekolah. Praktik ini juga diharapkan dapat meningkatkan tingkat disiplin, mengarah pada terciptanya lingkungan sekolah yang harmonis. Implikasi penelitian menunjukkan perlunya perbaikan dalam implementasi Budaya Piket Simpatik meningkatkan efektivitas dalam membentuk karakter. Hasil penelitian juga diharapkan memberikan panduan konstruktif untuk pengembangan lebih lanjut dari program pembentukan karakter di SMA Muhammadiyah 1 Ponorogo.